New Flap for the Reconstruction of the Perinasal Region - Doğan, Fatih; Özyazgan, İrfan (Facial Plastic Surgery, 2014)
Various reconstructive methods ranging from secondary healing to free flap applications are used for the reconstruction of perinasal defects caused by trauma or tumor surgery. The method to be used for the reconstruction of this region is chosen considering many factors because of specific determining structures. The number of studies on the subcutaneous tissue and vascular configurations of this region are gradually increasing along with the accumulation of knowledge in this region. Herein, we describe the nasal superficial musculoaponeurotic system–pedicled island skin flap for the reconstruction of the nasal tip, supratip, lateral nasal margin, and infraorbital area. The described skin flap was performed for defects resulting from basal cell carcinoma excision in all the patients. Of the patients, 12 were females and 5 were males. The mean age was 67.8 years (range, 56–82 years). All patients were operated on under general anesthesia. The flap donor areas were closed primarily. None of the patients developed flap necrosis. Although mild edema and venous insufficiency were observed in the flaps in the acute period only in patients who underwent nasal tip reconstruction, these improved during follow-up. In the operated patients, no problem was observed in the donor area and nasal dorsal skin. The nasal superficial musculoaponeurotic system–pedicled island skin flap which we describe for the perinasal area reconstruction is a safe, easily performed and versatile flap. The multidimensional use of this flap together with a relatively easy reconstruction plan and surgical procedure would be effective in flap choice.
Keywords: nasal reconstruction; SMAS flap; island skin flap